Aplikasi Kertas Bekas untuk Seed paper sebagai Kampanye Budaya Cinta Lingkungan di Desa Batu Belah Kecamatan Kampar - Utami, Syelvia Putri; Evelyn, Evelyn; Yusnimar, Yusnimar; Komalasari, Komalasari; Chairul, Chairul; Saputra, Edy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The increase in writing paper waste is quite large in office and educational areas. Likewise in households and the surrounding community. Therefore, the utilization of used paper into seed paper is an interesting thing to be tested in village communities. This community service activity aims to educate the community regarding the utilization of used paper into seed paper. This used paper is soaked in water then printed with a paper printing tool, then given flower seeds. The paper that is ready to be printed is then dried. Seed paper that is no longer used is then planted. This activity is expected to be an alternative to empowering used paper in the Batu Belah Village community, Kampar District.